PENGENDALIAN PERSEDIAAN MATERIAL UNTUK MEMENUHI SISTEM PRODUKSI MAKE TO ORDER MENGGUNAKAN MATERIAL REQUIREMENT PLANNING (MRP) - Nur Rahmawati; Ayu Aimmatus Sholichah (2477 - 6165, 2018)
CV. Dua Putra is a manufacturing company that categorized as a low medium enterprice. This company produces shoes such as futsal shoes, running shoes, casual, and also kids shoes. This company still using traditional inventory planning where component of their product will be bought when the stock is out. As a consequence there often be exceed and also run out of inventory in the storage. This research is aimed to plan material inventory for Airpro futsal on CV. Dua Putra. The method that is used in this reseach is Material Requirement Planning (MRP). Based on MRP result, the time required to complete demand in september is 34 days, 34 days for demand in October, and 23 days for demand in November.